NAFS DALAM PERSPEKTIF INSANIAH DAN TAHAPAN-TAHAPAN PENYUCIANNYA - Taufik Hasyim (LP2M IAI Miftahul Ulum Pamekasan, 2015)
Allah creates human consists of two substances, they are physical and spiritual substance. Physical substance is the physical appearance of human such as bone, skin, meat, hair, eyes, nail and many others parts of their body. While spiritual substance is disappear things such as mind, soul, desire, and heart. Those are called as soul in the sufism.Nafs or is often considered as something that is always comes to the ugliness, immorality, and injustice. Nafs is also considered as the object in every human mistakes, even nafs is also considered as partner of devil. But is it true? this article will discuss a bit of the nafs, kinds of nafs, the tendency of nafs and nafs purification phases that finally comes to a conclusion that nafs is essentially nature like a blank paper. The quality of nafs sometimes can be fluctuative depends on the behavior of the owner of nafs itself. If the nafs is often purified by mujahadah and riyadah, those nafs will come to the goodness, but it the nafs itself was never purified, then it will get low quality and come to immorality.